Zero tillage impacts on soil physical properties but not on crop yield - Sajjad Raza; Brian S. Atkinson; Imrul Hossain; Ho-Chul Shin; Hannah V. Cooper; Craig J. Sturrock; Andrew B. Riche; Malcolm J. Hawkesford; Sacha J. Mooney (European Journal of Agronomy, 2026)

Sediment transport modeling in Lake Ontario embayments: Impacts on fish spawning substrates - Ali Kheiri; Joseph F. Atkinson; Zhenduo Zhu; Lucas Le Tarte; Brian Weidel (Ecological Modelling, 2025)

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

A Paleocene occurrence of cornelian cherries Cornus subg. Cornus in the land-mammal site of Berru (Paris Basin, France) - Cédric Del Rio; Brian A. Atkinson; Thierry Smith (Review of Palaeobotany and Palynology, 2025)

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

New insights into pesticide occurrence and multicompartmental monitoring strategies in stream ecosystems using periphyton and suspended sediment - Moira M. Ijzerman; Melanie Raby; Nicholas V. Letwin; Yaryna M. Kudla; Jenna D. Anderson; Brian J. Atkinson; Rebecca C. Rooney; Paul K. Sibley; Ryan S. Prosser (Science of The Total Environment, 2024)

The effects of soil compaction on wheat seedling root growth are specific to soil texture and soil moisture status - Cailian Yu; Tinashe Mawodza; Brian S. Atkinson; Jonathan A. Atkinson; Craig J. Sturrock; Richard Whalley; Malcolm J. Hawkesford; Hannah Cooper; Xiaoxian Zhang; Hu Zhou; Sacha J. Mooney (Rhizosphere, 2024)

Life at the extreme: Plant-driven hotspots of soil nutrient cycling in the hyper-arid core of the Atacama Desert - Davey L. Jones; Bárbara Fuentes; Franko Arenas-Díaz; Francisco Remonsellez; Rutger van Hall; Brian S. Atkinson; Sacha J. Mooney; Roland Bol (Soil Biology and Biochemistry, 2023)

Soil structure has a greater effect on the rooting of wheat (Triticum aestivum L.) than nitrogen fertilisation rate or genotype - Tinashe Mawodza; Hu Zhou; Brian S. Atkinson; Jonathan A. Atkinson; Craig J. Sturrock; Andrew B. Riche; W. Richard Whalley; Malcolm J. Hawkesford; Hannah V. Cooper; Sacha J. Mooney (Rhizosphere, 2023)

Lethal and Sub-lethal Implications of Sodium Chloride Exposure for Adult Unionid Mussel Species: Eurynia dilatata and Lasmigona costata - Erika A. Burton; Brian Atkinson; Joseph Salerno; Hufsa N. Khan; Ryan S. Prosser; Patricia L. Gillis (Archives of Environmental Contamination and Toxicology, 2023)
The elevated use of salt as a de-icing agent on roads in Canada is causing an increase in the chloride concentration of freshwater ecosystems. Freshwater Unionid mussels are a group of organisms that are sensitive to increases in chloride levels. Unionids have greater diversity in North America than anywhere else on Earth, but they are also one of the most imperiled groups of organisms. This underscores the importance of understanding the effect that increasing salt exposure has on these threatened species. There are more data on the acute toxicity of chloride to Unionids than on chronic toxicity. This study investigated the effect of chronic sodium chloride exposure on the survival and filtering activity of two Unionid species ( Eurynia dilatata, and Lasmigona costata ) and assessed the effect on the metabolome in L. costata hemolymph. The concentration causing mortality after 28 days of exposure was similar for E. dilatata (1893 mg Cl − /L) and L. costata (1903 mg Cl − /L). Significant changes in the metabolome of the L. costata hemolymph were observed for mussels exposed to non-lethal concentrations. For example, several phosphatidylethanolamines, several hydroxyeicosatetraenoic acids, pyropheophorbide-a, and alpha-linolenic acid were significantly upregulated in the hemolymph of mussels exposed to 1000 mg Cl − /L for 28 days. While no mortality occurred in the treatment, elevated metabolites in the hemolymph are an indicator of stress.

Litter breakdown among intermittently connected and unconnected geographically isolated Wetlands: how nutrient inputs alter wetland function - Chelsea R. Smith; Stephen W. Golladay; Carla L. Atkinson; Brian A. Clayton (Wetlands, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Evolutionary history drives aspects of stoichiometric niche variation and functional effects within a guild - Carla L. Atkinson; Brian C. van Ee; John M. Pfeiffer (Ecology, 2020)
Functional traits are characteristics of an organism that represents how it interacts with its environment and can influence the structure and function of ecosystems. Ecological stoichiometry provides a framework to understand ecosystem structure and function by modeling the coupled flow of elements (e.g. carbon [C], nitrogen [N], phosphorus [P]) between consumers and their environment. Animals tend to be homeostatic in their nutrient requirements and preferentially sequester the element in shortest supply relative to demand, and release relatively more of the element in excess. Tissue stoichiometry is an important functional trait that allows for predictions among the elemental composition of animals, their diet, and their waste products, with important effects on the cycling and availability of nutrients in ecosystems. Here, we examined the tissue stoichiometric niches (C:N:P) and nutrient recycling stoichiometries (N:P) of several filter‐feeding freshwater mussels in the subfamily Ambleminae. Despite occupying the same functional‐feeding group and being restricted to a single subfamily‐level radiation, we found that species occupied distinct stoichiometric niches and that these niches varied, in part, as a function of their evolutionary history. The relationship between phylogenetic divergence and functional divergence suggests that evolutionary processes may be shaping niche complementarity and resource partitioning. Tissue and excretion stoichiometry were negatively correlated as predicted by stoichiometric theory. When scaled to the community, higher species richness and phylogenetic diversity resulted in greater functional evenness and reduced functional dispersion. Filter‐feeding bivalves are an ecologically important guild in freshwater ecosystems globally, and our study provides a more nuanced view of the stoichiometric niches and ecological functions performed by this phylogenetically and ecologically diverse assemblage.

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

Potential cardiovascular adverse events when phenylephrine is combined with paracetamol: simulation and narrative review - Hartley C. Atkinson; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Erratum to: Increased bioavailability of phenylephrine by co-administration of acetaminophen: results of four open-label, crossover pharmacokinetic trials in healthy volunteers - Hartley C. Atkinson; Ioana Stanescu; Isam I. Salem; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Increased bioavailability of phenylephrine by co-administration of acetaminophen: results of four open-label, crossover pharmacokinetic trials in healthy volunteers - Hartley C. Atkinson; Ioana Stanescu; Isam I. Salem; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Local adaptation to higher temperatures reduces immigration success of genotypes from a warmer region in the water flea Daphnia - WENDY VAN DOORSLAER; JOOST VANOVERBEKE; CATHY DUVIVIER; SARAH ROUSSEAUX; MIEKE JANSEN; BASTIAAN JANSEN; HEIDRUN FEUCHTMAYR; DAVID ATKINSON; BRIAN MOSS; ROBBY STOKS; LUC DE MEESTER (Global Change Biology, 2009)
There is growing awareness that microevolutionary dynamics may alter ecological processes. Rising temperatures under global change are expected to open windows for establishment of species and genotypes from warmer regions. Yet, microevolutionary tracking of temperature change by local populations may reduce establishment success of these immigrants. We exposed a UK population of the water flea, Daphnia magna , to two temperature regimes during a 1.5‐year experimental evolution trial, and subsequently compared competitive strength of non‐warm‐adapted and warm‐adapted D. magna in competition with French genotypes. Our results indicate that local microevolutionary responses to global warming may reduce establishment success of immigrant genotypes that are preadapted to warmer climate. Simulation modeling shows that microevolution results in a reduced likelihood and speed of displacement of local populations by immigrant genotypes under realistic immigrant/resident ratios. We conclude that local evolutionary dynamics may shift the relative impact of local and regional processes in response to global change.

Response of macroinvertebrates to warming, nutrient addition and predation in large-scale mesocosm tanks - Heidrun Feuchtmayr; Dermot McKee; Ian F. Harvey; David Atkinson; Brian Moss (Hydrobiologia, 2007)

Establishing the Canadian Community Monitoring Network - Graham Whitelaw; Hague Vaughan; Brian Craig; David Atkinson (Environmental Monitoring and Assessment, 2003)